An Error Analysis On Descriptive Text Made By Eighth Grade Students Of SMP N 2 Banyudono In 2013/2014 Academic Year - L Putra, Wahyu Azmi, Prof. Dr. Endang Fauziati, M. Hum, Dr. Dwi Haryanti, M.Hum (2014)
This study aims to describe the learners' error made by eight grade students of SMP N 2 Banyudono in their composition in writing descriptive text; identify the types of lexical errors, syntactical errors, and discourse errors; explain the frequency of each type of errors; describe the dominant type of errors; and identify the source of errors. The type of this research is descriptive qualitative research. In collecting the data the writer uses elicitation technique. There are some steps that the researcher does in collecting data, they are: the writer enter the class, the writer ask the students to write descriptive text, the writer reads the composition made by students accurately, the writer marks the erroneous sentences, then the writer lists the erroneous sentence and classifies the data into all types of error. in analyzing the data, the writer uses James theory for classification of errors, Slamet theory for the frequency of each type of error and Brown, Norish, Richard for sources of errors theory. The result of the research shows that eight grade students of SMP N 2 Banyudono still make 116 errors in their compositions. There are three classifications of error based on the combination of linguistic category taxonomy and surface strategy taxonomy. They are lexical error consists of 37, 05% that cover: wrong spelling 31, 89%, false friend (similar in form) 1, 72%, and use Indonesian word/ code switching 3, 44%. Syntactical error consists of 45,64% that cover: plural 6,03%, the use of verb tense 11,2%, BE 16,37%, pronoun 10,32%, article 1,72%. Discourse error consist of 17,24% that cover component of discourse in reference 17,24%. The researcher also finds 2 dominant sources of error, namely interlingual transfer and intralingual transfer. So, the students in SMP N 2 Banyudono especially eight grade students class A still make errors in their composition in writing descriptive text. The dominant error is syntactical error especially in BE from omission of BE as full verb.